Evolution of control of cross-listed companies. Issue 15 (7th December 2016) - Abdallah, Wissam; Goergen, Marc
Abstract : There are two theories on the determinants of the control structure of the firm. The first theory postulates that the control structure is determined by company-specific characteristics. The second theory emphasises the importance of institutional characteristics in shaping this structure. In this paper, we test the validity of both theories in the context of a cross-listing, which causes a change to the company's legal environment. We find that the initial control structure, risk and size determine the control structure post cross-listing and that cross-listing on better quality markets facilitates the evolution of control towards more dispersed control. To conclude, company characteristics have a greater impact than country characteristics on the company's decision to cross-list and are also better at explaining the change in the control structure post cross-listing.